British-Ottoman Trade Relations and the American Commercial Orientation Towards the Port of Smyrna 1740-1774 - Hussein, Zubaida Mohammed; Mahmoud, Idris Hardan (Journal of Ecohumanism, 2024)
The importance of trade relations between different countries was characterized by great importance as it is one of the means that contributed to cultural communication between peoples and nations, and some cities were often the key to that communication or a station for a global forum that contributed to the diversity of relations with which those countries were associated, and here comes the importance of the subject of the study to be traced. The history of one of the ancient cities with ancient historical depth, which is the city of Smyrna, a city that has a civilized history. It was one of the most important cities overlooking the Mediterranean Sea, and it brings together various cultural and economic activities. It has one of the most important ports in the world, as it has formed a forum for global trade since ancient times.